INNOVATION IN EDUCATIONAL TECHNOLOGY TO ENHANCE STUDENT LEARNING ACHIEVEMENT IN THE ERA OF THE MERDEKA CURRICULUM - Junarti; Husna Imro'athush Sholihah; Ratna Puspita Sari; Markus Oci; Ermy Dikta Sumanik (CV. ADIBA AISHA AMIRA, 2023)
This paper explored the implementation of educational technology as an innovative approach to improve student learning achievement within the context of the Merdeka curriculum. The study focused on the past experiences and outcomes of integrating educational schools successfully utilized online learning platforms and mobile applications to enhance student engagement, motivation, and learning outcomes. Online learning was introduced, providing students with easy access to learning materials and resources. Teachers were trained to utilize the platform and effectively provide online support to students. The implementation of the platform resulted in increased student engagement, motivation, and the flexibility to adapt learning to their own pace. The application facilitated independent and collaborative learning, enabling students to interact with teachers and classmates; implementing the mobile application led to improved student motivation, engagement, and overall learning achievement. The findings from these highlights the significance of adequate technological infrastructure, teacher training, integration of technology into lesson plans, and regular evaluation for effective implementation. These factors contribute to enhancing student learning achievement in the Merdeka curriculum era